Temporal variation in the summer diet of the weddell seal, leptonychotes weddellii, at hope bay, antarctic peninsula - Negri, A.; Daneri, Gustavo Adolfo; Coria, N. R.; Corbalán, A.; Negrete, Javier (Polar Biology)
The study of the feeding habits of Weddell seals, Leptonychotes weddellii, in the Antarctic Peninsula region is essential to understand their ecological role in the marine food webs, especially considering that this is one of the geographical areas most affected by climate change. The aims of this study were 1) to examine the diet of Weddell seals during the molting/resting stage of their annual cycle throughout five summer seasons 2) to assess the temporal variation in the diet composition 3) to determine the possible association of their feeding habits to climatic and oceanographic events such as El Niño Southern Oscillation ENSO and Southern annular mode (SAM). A total of 339 faecal samples were collected at Hope Bay between 2008/9 and 2013/14. Scat analysis indicated that, overall, fish constituted the dominant and most frequent prey taxon (F: 98.8%), followed by cephalopods (F: 33. 6%). Pleuragramma antarctica was the dominant and most frequent fish prey species representing, in average, 74.5% in numbers and 49.4% in mass of all the fish consumed. Cephalopods were mainly represented by the octopod Pareledone turqueti which represented, respectively, 53.7% and 56.8% in numbers and biomass of cephalopod prey consumed. Weddell seals preyed on demersal-benthic as well as pelagic resources. However, though octopods of the genus Pareledone were uniformly common as prey during the whole study period, P. antarctica became more dominant under negative SAM conditions and warm phase (El Niño) of ENSO. Fil: Negri, A. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Daneri, Gustavo Adolfo. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Coria, N. R. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección ...